PW 1507 Health action on gender, violence and life cycle. (November 2018) - Menezes, Barbara; Oliveira, Dina; Chaves, Nicole; Silva, Andreia; Figueira, Fátima; Prazeres, Vasco; Chaves, Marta; Machado, Daniela; Costa, Luísa Horta e; Mentes, Odete; Constantina, Maria; Marreiros, Maria; et al.
Abstract : The Health Action on Gender, Violence and Life Cycle, created through the order no. 6378/2013, aims to homogenize the national intervention and potentiate the interventions already developed in the health services that are considered good practices in the field of violence. It also intends to promote equality, particularly health equity, and prevent interpersonal violence in adults, through the functional articulation with other like structures in the health services and in the community. This integrated model of intervention on interpersonal violence cases in health settings is considered good practice by the European Institute for Gender Equality. As a result of the creation of the Health Action on Gender, Violence and Life Cycle, in the National Health Service, at December 2016, were created 224 Teams of Prevention of Violence in Adults at national level (Primary Health Care and Hospitals). In the course of the same year, were signaled 2434 new cases of interpersonal violence in the TPVA, of those: 25% concern to males and 75% to females; In a study of partial data, corresponding to 3 of the 5 Regional Health Administrations, of the cases identified as domestic violence (554 cases), 15% of the victims were male and 85% were female victims. Considering that interpersonal violence is a common problem in intimate and family relationships emerged the need to define protocols for structured intervention. Therefore, the technical guide for Interpersonal Violence – approach, diagnosis and intervention in health services was created as a tool to support health professional throughout the whole process. This technical guide for health professionals also allows a better articulation in the services once it makes the institutional resources profitable, as well as the definition of circuits, like flowcharts, to intervene in interpersonal violence.